8:2 Fluorotelomer alcohol causes G1 cell cycle arrest and blocks granulocytic differentiation in HL‐60 cells. Issue 5 (22nd February 2019) - Wang, Xia; Zhou, Chenqian; He, Bingnan; Kong, Baida; Wei, Lai; Wang, Rong; Lin, Jiajia; Shao, Yiyan; Zhu, Jianbo; Jin, Yuanxiang; Fu, Zhengwei
Abstract: Fluorotelomer alcohols (FTOHs) are fluorinated intermediates used in manufacturing specialty polymer and surfactants, with 8:2 FTOH the homologue of largest production. FTOHs were found to pose acute toxicity, hepatotoxicity, nephrotoxicity, developmental toxicity and endocrine‐disrupting risks, whereas research regarding immunotoxicity and its underlying mechanism, especially on specific immune cells is limited. Here, we investigated the immunotoxicity of 8:2 FTOH on immature immune cells in an in vitro system. We observed that exposure of HL‐60 cells, a human promyelocytic leukemic cell line, to 8:2 FTOH reduced cell viability in a dose‐ and time‐dependent manner. In addition, 8:2 FTOH exposure caused G1 cell cycle arrest in HL‐60 cells, while it showed no effect on apoptosis. Exposure to 8:2 FTOH inhibited the mRNA expression of cell cycle‐related genes, including CCNA1, CCNA2, CCND1, and CCNE2 . Moreover, exposure to 8:2 FTOH inhibited the mRNA expression of granulocytic differentiation‐related genes of CD11b, CSF3R, PU.1, and C/EPBε in HL‐60 cells . Furthermore, 8:2 FTOH exhibited no effect on intracellular ROS level, while hydralazine hydrochloride (Hyd), one reactive carbonyl species (RCS) scavenger, partially blocked 8:2 FTOH‐caused cytotoxicity in HL‐60 cells. Overall, the results obtained in the study show that 8:2 FTOH poses immunotoxicity in immature immune cells and RCS may partially underline its mechanism.